THE INFLUENCE OF WORK STRESS, WORKLOAD, AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE AT THE WONOKROMO URBAN VILLAGE OFFICE - Nur Anisa Fitri; Sugiyanto, Sugiyanto (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
This study aims to determine and analyze: (1) the effect of work stress on employee performance at Wonokromo Ward/Village Office; (2) the effect of workload on employee performance at Wonokromo Ward/Village Office; (3) the effect of work discipline on employee performance at Wonokromo Ward/Village Office; and (4) the effect of work stress, workload, and work discipline simultaneously on employee performance at Wonokromo Ward/Village Office. This research includes causal associative using an associative approach. This research is categorized as survey research, where the research instrument is a questionnaire. The sample in this study were employees of the Wonokromo Ward/Village Office, totaling 24 people. The instrument validity test uses r-count ≥ r-table, while the reliability test uses Cronbach’s Alpha ≥ 0,60, and data analysis is carried out at 5% significance showing that: (1) work stress has a positive value but insignificant effect in employee performance at the Wonokromo Ward/Village Office with a t-count value of 0.613 < 1.721 and a significance of 0.547 > 0.05; (2) workload has a positive value but insignificance effect on employee performance at Wonokromo Ward/Village Office with a t-count value of 0.382 < 1.721 and a significance of 0.707 > 0.05; (3) work discipline has a positive value and significant effect on employee performance at the Wonokromo Ward/Village Office with a t-count value of 1.906 > 1.721 and a significant of 0.01 < 0.005; and (4) work stress, workload, and work discipline simultaneously have a positive value and significant effect on employee performance at the Wonokromo Ward/Village Office with an F-count value of 4.477 > 3.10 and a significance of 0.00.